ANALISIS FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA SEKTOR CONSUMER AND GOODS - Auliya Eka Puji Lestari (2021)
This study aims to determine the effect of profitability, company growth, leverage, earnings, and also business risk on dividend policy. The research was conducted on the sector consumer and goods listed on the Indonesian Stock Exchange (IDX) in 2016-2020. By using purposive sampling method, the research sample obtained is 21 companies. The technique used in analyzing the data is Panel Data Regression Analysis with the help of the program Eviews 12. The results obtained are Profitability as measured by Return On Equity (ROE) proven to have an effect on Dividend Policy, Company Growth as measured by Growth Assets proven to have an effect on Dividend Policy, Leverage as measured by Debt To Equity Ratio proven to have an effect on Dividend Policy, Earning as measured by Earning Per Share(EPS) is proven to have no effect on Dividend Policy, and Business Risk as measured by Business Risk (BRISK) is proven to have no effect on Dividend Policy.